KAJI EKSPERIMENTAL PENGARUH KAPASITAS KONDENSATOR DAN JUMLAH PLAT STAINLESS STEEL ELEKTROLISER TERHADAP DAYA HONDA SUPRA X 125 CC TAHUN 2013 SEBAGAI BAHAN AJAR TEKNIK SEPEDA MOTOR - Irawan, Riky (Jurnal Nosel, 2015)
The aims of this research are : (1) To investigate the effect of using electrolyzer with variety of condensator capacity to engine power of Honda Supra X 125 cc in 2013. (2) To investigate the effect of using electrolyzer with variety number of stainless steel plate to engine power of Honda Supra X 125 cc in 2013. (3) To investigate the effect of interaction variety condensator capacity and using electrolyzer with variety number of stainless steel plate to engine power of Honda Supra X 125 cc in 2013. This research was quantitative research with experimental method. This research was conducted at Mototech Motocourse Technology, Ringroad Selatan, Kemasan, Singosaren, Banguntapan, Bantul, Jogjakarta. The equipment that was used to measure engine power was Sportdyno V3.3. The population of this research was Honda Supra X 125 cc in 2013 and the sample of this research was Honda Supra X 125 cc in 2013 with JB91E3233452 engine number. This research was analyzed two-way analysis of variance. This research was using variety of condensator capacity : 1,000 F, 2,200 F, 3,300F and variety of stainless steel plates number : 8 plates, 10 plates, 12 plates. Based on this research the conclusion were : (1) There was an effect of condensator capacity electrolyzer to engine power of Honda Supra X 125 cc in 2013. It was showed in the result of analysis test that stated Fe = 5 more bigger than Ft = 3.55 (Fe > Ft) in 5% significancy. (2) There was an effect of electrolyzer stainless steel plate number to engine power of Honda Supra X 125 cc in 2013. It was showed in the result of analysis test that stated Fe = 5 more bigger than Ft = 3.55 (Fe > Ft) in 5% significancy. (3) There was an interaction of condensator capacity and number of electrolyzer stainless steel plate to engine power of Honda Supra X 125 cc in 2013. It was showed in the result of analysis test that stated Fe= 4 more bigger than Ft = 2.93 (Fe> Ft) in 5% significancy. (4) Maximum engine power of Honda Supra X 125 cc in 2013 as big as 9.1 HP from using 3,300 F condensator and 12 plates electrolyzer.